Fotografiks in cover design of music albums (1970s–2010s) in the context of André Rouillé’s ideas - A. Yu. Pronina (Шаги)
The article discusses the practice of using photographs in graphic design and reveals the concept of fotografiks as a special approach to working with photography. The lack of extensive research in the field of fotografiks makes the study of photographs in design highly relevant. We demonstrate a process for defining a structure from different types of images and then building systems through which photography works in design and which can be used for practical purposes. To analyze fotografiks, the author uses the method of extrapolation: she transfers the idea of the French art critic André Rouillé about the four functions of photography to the special case of its use in graphic design. André Rouillé’s book, Photography: Between document and contemporary art, is analyzed. The article examines and analyzes the four functions that Rouillé writes about: photography as document, photography as expression, photography as tool, and photography as material. Photography as a document reveals a close connection with the referent, denotes what is depicted, and is often used in design projects. Photography as expression is capable of imparting more meaning to an image than an ekphrastic reading of that image, and is used to create atmospheric images with hidden meanings and details. Photography as tool gives designers a powerful toolkit for constructing new images. Photography as material allows one to create design projects comparable to works of art in terms of the depth of their concept and implementation. Each of these functions is discussed using examples of music album cover design from the 1970s– 2010s. Based on the results of the study, the author concludes that A. Rouillé’s proposal to consider photography through its functions is applicable both in design theory, for the study of created works, and in practical applications in the field of graphic design.